Pengaruh Dana Pihak Ketiga (DPK), Financing to Deposit Ratio (FDR), Non Performing Financing (NPF) dan Return on Asset (ROA) Terhadap Total Aset Perbankan Syariah di Indonesia - Ariani, Rikka Sri; Parno, Parno; Pratiwi, Angrum (Institut Agama Islam Negeri Ponorogo, 2022)
The development of the Islamic banking industry since long ago until now shows that the growth is satisfactory one of them in terms of assets. Islamic banking must maintain the quality of assets to achieve expected profits. With the increase in the quality of assets expected, so as to improve the bank's performance and achievement in profit. The increase in Islamic banking in total assets is influenced by several factors including DPK, FDR, NPF and ROA. To find out the development of Islamic banking in Indonesia. This research aims to find out the influence of Third Party Funds (DPK), Financing to Deposit Ratio (FDR), Non Performing Financing (NPF) and Return On Asset (ROA) of Islamic banking in Indonesia, both partially and simultaneously.The study used a decryptive method of analysis with a quantitative approach. The population used as many as 197 populations with sampling techniques that are saturated sampling so that the number of samples used as many as 197 samples. Data collection techniques use documentation techniques in the form of monthly reports by accessing Islamic banking statistics published by OJK. The analytical method used is multiple regression analysis.The results showed that Third Party Funds (DPK) had a significant effect on Total Islamic Banking Assets in Indonesia, Financing to Deposit Ratio (FDR) had a significant positive effect on Total Islamic Banking Assets in Indonesia, Non Performing Financing (NPF) negatively affect Total Islamic Banking Assets in Indonesia, Return On Asset (ROA) had no effect on Total Islamic Banking Assets in Indonesia and DPK, FDR, NPF and ROA simultaneously affect the total assets of Islamic banking in Indonesia.Perkembangan industri perbankan syariah sejak dulu hingga sekarang menunjukkan bahwasannya pertumbuhan yang memuaskan salah satunya dari segi aset. Perbankan syariah harus menjaga kualitas asetnya untuk mencapai laba yang diharapkan. Dengan meningkatnya kualitas aset yang diharapkan, sehingga dapat meningkatkan pula kinerja bank maupun pencapaian pada laba. Peningkatan perbankan syariah dalam total aset dipengaruhi beberapa faktor diantaranya DPK, FDR, NPF dan ROA. Guna mengetahui perkembangan yang terjadi perbankan syariah di Indonesia. Penelitian ini bertujuan untuk mengetahui pengaruh Dana Pihak Ketiga (DPK), Financing to Deposit Ratio (FDR), Non Performing Financing (NPF) dan Return On Asset (ROA) perbankan syariah di Indonesia, baik secara parsial maupun simultan.Penelitian ini menggunakan metode dekriptif analisis dengan pendekatan kuantitatif. Populasi yang digunakan sebanyak 197 populasi dengan teknik pengambilan sampel yaitu sampling jenuh sehingga jumlah sampel yang digunakan sebanyak 197 sampel, periode pengamatan tahun 2016-2020. Teknik pengumpulan data menggunakan teknik dokumentasi berupa laporan bulanan dengan mengakses statistik perbankan syariah yang di terbitkan oleh OJK. Metode analisis yang digunakan yaitu analisis regresi berganda. Hasil penelitian menunjukkan bahwa Dana Pihak Ketiga (DPK) berpengaruh potif signifikan terhadap Total Aset Perbankan Syariah di Indonesia, Financing to Deposit Ratio (FDR) berpengaruh positif signifikan terhadap Total Aset Perbankan Syariah di Indonesia, Non Performing Financing (NPF) berpengaruh negatif terhadap Total Aset Perbankan Syariah di Indonesia, Return On Asset (ROA) tidak berpengaruh terhadap Total Aset Perbankan Syariah di Indonesia dan DPK, FDR, NPF dan ROA secara simultan berpengaruh terhadap total aset perbankan syariah di Indonesia.